Laurence Moon Bardet Biedle Syndrome - Islam, Md Nazrul; Akhter, Shamima; Kamal, SM; Chowdhury, Sabikun Nahar (Medicine Today, 2018)
Laurence Moon Bardet Biedle syndrome is a rare, autosomal recessive genetic disorder involving multiple systems and has wide spectrum of clinical features. Characteristic features of this disorder are retinitis pigmentosa, polydactyly, truncal obesity and learning difficulties. It may also be associated with hypogonadism in male and complex genitourinary abnormalities in female. We present a case of 33 years male patient having obesity, decreased vision, polydactyly, hypogonadism and retinitis pigmentosa. These clinical features are consistent with Laurence Moon Bardet Biedle syndrome. Medicine Today 2018 Vol.30(1): 41-43